PENERAPAN MODEL LATIHAN PASSING DENGAN METODE SMALL SIDE GAMES PADA KELOMPOK USIA U-12 - Mahfud, Imam; Nugroho, Reza Adhi (SPORT SCIENCE AND EDUCATION JOURNAL, 2024)
The aim of this research is to determine the improvement of passing skills through the small side games training method in the U-12 age group. This research is using experimental method. The sample in this study was SSB students in the 12 year age group, totaling 30 people. Based on the research results, it can be seen that training using this method has a significant impact on passing results. This can be seen from the results of calculating the data obtained. The research results showed that the average difference in passing skills in the initial test was 6.84 and the final test was 7.98. The T test results show a calculated T value of 7.594> from a T table of 2.045 with a significant value of 0.00 <0.05. The conclusion of this research is that training in passing using the small side games method improves passing skills in the Age 12 group.